Solvitur Ambulando. A brief history of production and use of artificial limbs - Willem J. Mulder (Acta Medico-Historica Rigensia)
"I’ve done it! Have just come in from a 10-mile walk! The best I’ve done yet. Time 2 hrs 40 mins – not racing time, I am afraid, but I hope to improve on it. My Hanger is doing very good service. I can never be too grateful to Hangers for the skill and patient care with which they fitted me, and also for the sympathy and kindness shown to me. The loss of a limb can never be exactly a joke, and it makes a wonderful difference when your fitters realise that their work has a human as well as a technical aspect." So far a citation of an enthusiastic miss G. G. Vaughan from Lincoln, England. She is talking obviously about her artificial leg that was produced and fitted by the Firm J. E. Hanger & Co Ltd in Roehampton, London in 1936.